A study on the factors that stimulate economic growth in Malaysia / Muhammad Syahiman Ghazalle and Khairun Nisa Mohd Mispan - Ghazalle, Muhammad Syahiman; Mohd Mispan, Khairun Nisa (Faculty of Business and Management, 2016)
The purpose of this study is to investigate the factors that stimulate economic growth which are export revenue, government consumption, gross fixed investment, public debt and private consumption in Malaysia. The data was collected in quarterly basis from year 1996 to 2013. This study used Single Linear Regression and Multiple Linear Regression in order to determine the relationship among these variables. Based on the result, it reveals that for all independent variables which are export revenue, government consumption, gross fixed investment and private consumption have a significant positive relationship towards economic growth which represented by gross domestic product. Meanwhile, the result for public debt has a same existing literature that found a negative relationship towards economic growth.